Never get a "real" job : how to dump your boss, build a business, and not go broke - Gerber, Scott, 1983- (Wiley, 2011)
"Go to work for the best boss in the world-yourself Never Get a "Real" Job challenges the social conventions behind the old-school, 9-to-5 "real" job, and empowers entrepreneurs to take control of their lives, fears, and careers. Successful entrepreneur Scott Gerber dissects failures, shares hard-learned lessons, and presents practical, affordable, and systematic action steps to building, managing, and marketing a successful business that accompanies being your own boss. The proven no-holds-barred approach presented in Never Get a "Real" Job teaches aspiring entrepreneurs, small business owners, students and recent college graduates how to quit the rat race and achieve financial independence without going broke. Author Scott Gerber is not the product of a wealthy family or storied entrepreneurial heritage. Nor is he the outcome of a traditional business school education or a corporate executive turned small business owner. Rather, he is an authentic, self-taught entrepreneur who has survived and thrived despite never holding a "real" job. Start your business based on your passions using the included self-assessment tools that include tips on how to make the leap between the dream and the doing without breaking the bank. Successfully transition into being your own boss, and never work in anyone else's office again with Never Get a "Real" Job."--